Development and Validation of Inorganic Phosphorus Test Kit in Rubber Latex - Sawaraj, Sunanta; Khawmee, Khwunta; Seechamnanturakiy, Vatcharee; Poonpakdee, Chakkrit; Onthong, Jumpen (YRU Journal of Science and Technology, 2021)
Inorganic phosphorus (Pi) in latex can reflect activity of latex synthesis and rubber tree health. However, Pi analysis is generally conducted in a laboratory that requires analytical instrument. The objective of this study was to develop latex Pi test kit that is easy to use with high accuracy. The latex serum and phosphorus standard solution were used for the determination of optimum conditions for the development of the test kit and then Pi level measured by test kit was compared with a laboratory method. The results showed that vanadomolybdate method was stable for color development. This method used 0.5 ml of sample, adding 3 ml of color reagent, shaking well, and after 3 minutes assessing the level of Pi with a color chart. Pi level measured by this test kit was highly correlated with laboratory methods (r = 0.898). Using this test kit to evaluate Pi level in rubber tree latex RRIM 600 in 13 rubber plantations that contain low and medium Pi level, it was found that the average accuracy percentage was 70 and 62. Therefore, the Pi test kit can be used to assess the levels of Pi in latex. It is convenient, quick and inexpensive. It can be used as a guideline for rubber tree management and rubber yield potential evaluation.